2004
DOI: 10.1002/polb.20131
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thin polymer‐like films formed by plasma polymerization of methylmethacrylate: A neutron reflectivity study

Abstract: The microstructure of the plasma‐polymerized methylmethacrylate (ppMMA) films is characterized using neutron reflectivity (NR) as a function of the plasma reaction time or film thickness. Variation in the crosslink density normal to the substrate surface is examined by swelling the film with a solvent, d‐nitrobenzene (dNB). In the presence of dNB, uniform swelling is observed throughout the bulk as well as at the air surface, and silicon oxide interfaces. The results indicate that the MMA film prepared by plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Compared to plasma films deposited from MMA [6,8,11,12,37±39] based on FTIR results, the high-flow iCVD sample in this work exemplifies much more structural resemblance to conventional PMMA than the plasma samples. FTIR studies of plasma films have shown broadened peaks, [8,11,38] diminished C=O peaks, [8,39] and weakened C±O and C±H peaks.…”
Section: Resultsmentioning
confidence: 97%
“…Compared to plasma films deposited from MMA [6,8,11,12,37±39] based on FTIR results, the high-flow iCVD sample in this work exemplifies much more structural resemblance to conventional PMMA than the plasma samples. FTIR studies of plasma films have shown broadened peaks, [8,11,38] diminished C=O peaks, [8,39] and weakened C±O and C±H peaks.…”
Section: Resultsmentioning
confidence: 97%
“…[2,3,6,15,16] These films also show very broad O-H stretching centered near 3400 cm -1 that, combined with the broad carbonyl peak, is more representative of poly(carboxylic acid) than PMMA. Conversion of the methoxy ester to carboxylic acid is possible via scission of the C-OCH 3 bond, creating a radical site which can then react with water in the deposition chamber or upon exposure to air to form the -COOH moiety.…”
Section: Ftir Spectroscopy To Determine the Optimal W/fmmentioning
confidence: 94%
“…[11] Thin films of PMMA have been created using spin-on, [1,12] laser-assisted vapor deposition, [13] and PECVD. [3][4][5][6][7]11,[14][15][16][17][18] Utilizing its clean and nearly complete thermal degradation, and its properties as an e-beam resist, PMMA has the potential to be a directly patternable sacrificial material for fabrication of closed cavity, air-gap structures which have applications in photonics and in semiconductor devices as an ultra low-k dielectric. This work examines the structure of films deposited under continuous wave (CW) and pulsed plasma-enhanced (PPE) CVD from MMA monomer under various processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional surface characterization techniques that are commonly employed in the field do not quantify the amount of hydrogen remaining in plasma polymer films after plasma polymer deposition. Reflectometry techniques are now becoming increasingly important in the characterization of these nano-scale interfaces [21][22][23][24]. X-ray reflectometry (XRR) is ideally suited to the study of the internal properties of layered film structures on surfaces, yielding data on sub-surface structure and material properties.…”
Section: Introductionmentioning
confidence: 99%